Challenges in diagnosing hydatidiform moles: a review of promising molecular biomarkers. (3rd August 2022) - Zhao, Yating; Huang, Bo; Zhou, Lin; Cai, Luya; Qian, Jianhua
ABSTRACT: Introduction: Hydatidiform moles (HMs) are pathologic conceptions with unique genetic bases and abnormal placental villous tissue. Overlapping ultrasonographical and histological manifestations of molar and non-molar (NM) gestations and HMs subtypes makes accurate diagnosis challenging. Currently, immunohistochemical analysis of p57 and molecular genotyping have greatly improved the diagnostic accuracy. Areas covered: The differential expression of molecular biomarkers may be valuable for distinguishing among the subtypes of HMs and their mimics. Thus, biomarkers may be the key to refining HMs diagnosis. In this review, we summarize the current challenges in diagnosing HMs, and provide a critical overview of the recent literature about potential diagnostic biomarkers and their subclassifications. An online search on PubMed, Web of Science, and Google Scholar databases was conducted from the inception to 1 April 2022. Expert opinion: The emerging biomarkers offer new possibilities to refine the diagnosis for HMs and pregnancy loss. Although the additional studies are required to be quantified and investigated in clinical trials to verify their diagnostic utility. It is important to explore, validate, and facilitate the wide adoption of newly developed biomarkers in the coming years.